RISK FACTORS AND REFERENCE VALUES OF ANTIBIOTIC RESIDUES IN IMPORTED RED MEAT AND THEIR IMPACTS ON GENOTOXICITY AND DNA DAMAGE IN HUMAN LYMPHOCYTES - May R. Hawas,; Firas R. Al-Samarai, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Antibiotic residues in food are accelerate the development of antibiotic resistance in bacteria, transfer of antibiotic-resistant bacteria to humans, cause allergies (penicillin), and cancers. This study was designed to investigate the risk factors of some antibiotic residue in imported red meat at Baghdad markets, their reference values, and their impact on genotoxicity and DNA damage in human cells.Atotalof144 meat samples were collected from January to July 2022.The results showed that the overall contamination percentage was35.4%. Buffalo meat showed the lowest contamination percentage 15% whereas the minced beef showed the highest (94.5%) (OR=402.33).Tetracycline residues detected in 42.8% of samples with significant risk (P=0.0001)(OR=33.37;95%CI=7.74-143.94).The mean of tetracycline was 83.80 ppb with lower and upper limits of 56.7, 110.9 ppb, respectively. Blood samples of 18 healthy males were used to isolate lymphocytes to detect the genotoxicity and DNA damage of antibiotic residues. Results showed significant effects of antibiotic residues on genotoxicity and human DNA damage. These results also showed that although the antibiotics residues concentrations are below the allowed maximum residues limit, this does not reduce the hazards of these residues on public health resulting from their accumulative increase in consumers' tissues.